KS05.6.A Oral DNA vaccination targeting VEGFR2 combined with the anti-PD-L1 antibody avelumab in patients with progressive glioblastoma - final results. NCT03750071. (5th September 2022) - Wick, W; Wick, A; Chinot, O; Sahm, F; von Deimling, A; Jungk, C; Mansour, M; Podola, L; Lubenau, H; Platten, M
Abstract: Background: Vascular endothelial growth factor receptor (VEGFR)2 overexpression on glioblastoma endothelia serves as a target for VEGFR2 primed T cells using VXM01 DNA vaccine encoding for VEGFR2. VXM01 is delivered in a bacterial Ty21a carrier suitable for oral administration. A previous phase I/II study in 14 patients with progressive glioblastoma showed a positive correlation of of VEGFR2 specific T cells as well as altered intra-tumoral immunity with prolonged overall survival. One partial response was reported with VXM01 alone. The current trial aimed at intensifying the efficacy signal and testing the co-administration of a checkpoint inhibitor. Material and Methods: A multicentre, open-label phase I/II study (EudraCT 2017 003076 31) included 28 patients (25 non-resectable, 3 resectable) with progressive glioblastoma after standard chemoradiotherapy. VXM01 was administered on day 1, 3, 5, 7 followed by boostings q4w. Avelumab (800 mg) was given intravenously q2w. Treatment continued up to week 96 followed by a 2-year observation period. Endpoints included safety and tolerability, objective response rate (ORR), clinical response using immune-response assessment in Neurooncology criteria (iRANO), and immunological assays like ELISpot, FACS, and tumor immune biomarkers. Results: Treatment with VXM01 10 6 or 10 7 CFU plus avelumab was completed in all patients. No treatment-related toxicities were observed. Three partial responses (according to iRANO) with tumor reductions of 58, 81 and 95% to baseline, respectively, were reported in the non-resectable patients (Objective response rate (ORR) was 12% (3/25)). Two of these patients were progression-free > 12 months. Best response in 3 additional non-resectable patients was SD including one patient progression-free > 6 months. In one resected patient, tumor shrinkage of 30% each was observed after initial treatment before resection as well as subsequent to incomplete resection, associated with survival > 18 months, and accompanied by an increase of intratumoral CD8+ T-cells. Conclusion: VXM01 in combination with avelumab was safe and produced detectable peripheral VEGFR-2-specific immune responses. Three non-resected patients had an objective response, three more patients experienced best response stable disease. For future studies a patient enrichment strategy based on immune biomarkers might be envisaged.